2023
DOI: 10.15639/teflinjournal.v34i1/21-38
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Remote Teaching in Indonesia: A Missed Opportunity for Greater Learner Autonomy

Abstract: The sudden switch to learning from home during the COVID-19 pandemic impacted teachers across the world. In Indonesia, schools were closed from early March 2020 onwards. This paper presents the findings of a qualitative research project that investigated how Indonesian teachers of English responded to the challenges of Emergency Remote Teaching (ERT) and whether ERT would lead to greater learner autonomy. Ten teachers responded to an invitation to participate in focus groups and individual interviews on Zoom a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…(2023) believed that the shifting from traditional face-to-face teaching to remote and online learning could cause greater learner autonomy. However, the traditional teacher-centered learning in Indonesia that emphasized the didactic nature showed that the learners' autonomy might not be ready to be promoted (Defianty & Wilson, 2023).…”
Section: Riyani Et All (2023)mentioning
confidence: 99%
“…(2023) believed that the shifting from traditional face-to-face teaching to remote and online learning could cause greater learner autonomy. However, the traditional teacher-centered learning in Indonesia that emphasized the didactic nature showed that the learners' autonomy might not be ready to be promoted (Defianty & Wilson, 2023).…”
Section: Riyani Et All (2023)mentioning
confidence: 99%